Desempenho agronômico e nutricional do capim "Mulato II" sob doses e fontes de nitrogênio - Jacovetti, Reginaldo (2016)
Aiming a commercial competitiveness to the brazilian final product, in the current situation, the beef cattle industry shows itself as the largest herd in the world, but with low production by area. To Brazil improve zootechinical indexes, is necessary to product with knoledge, enviromental sustainability and first of all respecting the limits of all involved in the process like wather, soil, environment, plant, plant and man. Amomng this limits we need to respect all productive process of each regional structure and comerce for example large curlures, horticulture and livestock. If not respected this limits and regional structure is compromised the economical part of the system. To produce beef we need a lot o sources like wather "scarce resource" , agricultural area, and so cattle as feeded by grass, what kind of feed could be inserted in each region, and finaly we bring the knowledge that we need informations like local annual precipitation, maximun and minimum temperature, informations about phisical and chemical characteristics os the soil to be secure about your investiment. To animal production is required specific knowledge to produce without degradate the environment, making the zootechical indexes persist, respectiong the plant limit production, aminal limit production and environmental sustainability. There are many forrage cultivars to pasture, among them a recently released hybrid Brachiaria genotype "Convert HD 364" cv Mulato II, that requires research to identify the type of growth, production per area of dry matter and bromatological parameters to define the forrage production potencial. So was analysed the total area production, laboratory analyses to characterize the bromatological production, apparent nitrogen recover and total crude protein production of Mulato II. To qualitative analyse was made a in situ and in vitro gas production of Mulato II grass.